The Idea of the Politics of Realisation in José Ortega y Gasset - Leszczyna, Dorota Maria (Daimon Revista Internacional de Filosofia, 2019)
The goal of my article is to present the idea of the politics of realisation as defined by Ortega. This philosopher made his mission the fight for “new vital Spain” that could be made real through its Europeanisation. The vision of political activities proposed by Ortega was different from the traditional one. It was not focused on soliciting for votes and keeping the power but its goal was to exploit the potential of the nation and to grow the vitality of Spain. Such perspective of ‘Politics’ became for Ortega the politics of realisation. It was the result of overcoming political idealism and naïve realism. Ortega abolished the aforementioned standpoints and specified his own project of critical realism in the form of the politics of realisation. For him, the realisation means the “higher imperative in the area of politics”. It draws the attention to the fact that the purpose already includes the realised activity. It does not act against the ideal but draws it from the real structure of things and not from our subjective desires and ideas.